EXPERIENCE OF FOREIGN INVESTMENT ACTIVITY OF INSURANCE COMPANIES - R. Pikus; D. Nesterova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article presents the experience of the investment of insurance companies of developed foreign countries. Specific features of state regulation of investment activities of insurance companies are determined, as well as described the main trends shaping the investment portfolio of the insurer under current conditions.